التربية الإسلامية والتسامح : شيئان متكاملان - HICHEM GRISSA (TAWASUT, 2019)
Abstract This article tries to uncover the relationship between education and tolerance, the points in common between the two and the mutual influence between them. By using descriptive analysis method, the writer elaborates matters related to education, such as basics, elements, media and methods. In terms of tolerance, the writer traces the roots of these words in Arabic and the extent to which they are related to the meaning of the vocabulary (tolerance) in English. This article finds that education, both from an epistemological and axiological perspective, is closely related to tolerance. For example, in terms of understanding. Education in a simple sense is the process of forming students to become better. This process, of course, requires an adequate attitude of tolerance from educators in dealing with students. Likewise in the elements of education, such as universality, egalitarianism, graduation, comprehensive, realistic, sustainable. The application of these educational elements cannot be realized except through a tolerant view and attitude. Where the simplistic definition of tolerance is not imposing punishment on the party who should get it, not demanding the rights of the party that should have been obtained due to humanitarian considerations. This is the highest meaning of education too.